Serum and Saliva Myelin Basic Protein as Multiple Sclerosis Biomarker - Mohammad Hossein Mirzaii-Dizgah; Mohammad Reza Mirzaii-Dizgah; Iraj Mirzaii-Dizgah (Basic and Clinical Neuroscience, 2021)
Introduction: Multiple Sclerosis (MS) is presented with motor and sensory function loss. It is caused by demyelination and following axonal lesion. As Myelin Basic Protein (MBP) is one of the key elements of the myelin cover, we examined the level of MBP in serum, stimulated, and unstimulated saliva as a suitable biomarker for detecting MS. Methods: A case-control study was performed in 29 healthy women and 32 definitive relapsing-remitting MS patients hospitalized in Imam Reza hospital, Tehran, Iran. MBP level was assayed in serum and stimulated and unstimulated whole saliva. Results: MBP was expressed at a lower level in serum and stimulated saliva of MS patients compared to the control group. The serum MBP level had a considerable correlation with its stimulated saliva level. The receiver operating characteristic analysis showed significant diagnostic ability for MBP to discriminate MS patients with serum and stimulated saliva from controls. Conclusion: Serum and saliva level of MBP is lower in MS, so it may be considered a potential biomarker in MS.